Kualitas Arang Kompos Limbah Industri Kertas dengan Variasi Penambahan Arang Serbuk Gergaji The qualities of Compost Charcoal Manufactured from Paper-mill Waste with Varying Addition of Charcoal Sawdust - Sri Komarayati; Mustaghfirin Mustaghfirin; Kurnia Sofyan (Masyarakat Peneliti Kayu Indonesia, 2007)
The development of paper and pulp industry cause waste handling problem. A kind of waste that needs serious attention is sludge. Sludge handling by burning causes air pollution problem, while land filling need much more infestations and areas. Therefore, composting believed as the most effective way to handle sludge. The objective of this research is to increase sludge product utility and to know quality of compost charcoal from sludge. The materials used are sludge from PT Indah Kiat Pulp and Paper Tangerang, Banten, saw dust, saw dust charcoal, and particular bio- activators called OrgaDec were used to stimulate the decomposition of those materials. The methods used are total carbon, nitrogen, phosphor (P2O5), kalium (K2O), magnesium (MgO), cation exchange capacity (CEC) and total Calcium (CaO). The best composting pH and temperature is treatment without charcoal addition. The treatment made pH and temperature goes down by charcoal addition. Analysis quality of compost charcoal show that charcoal addition will cause increasing of CEC and decreasing C/N ratio.